OPTIMIZATION OF LENGTH OF LOWER EXTREMITIES IN HIP REPLACEMENT - V. A. Shil’Nikov; V. A. Neverov; A. O. Denisov; I. I. Shubnyakov (Вестник хирургии имени И.И. Грекова, 2016)
An analysis of results of endoprosthesis was made in 93 patients with initial shortening of lower extremity more than 3 cm. There were revealed the main factors influencing on the result and developed the criteria of prediction of adjustment of extremity length such as assessment of duration of the disease, presence of implications of earlier performed operations, sex, age, degree of tissue rigidity, evidence of hip-spine syndrome and scoliosis.